ASPECTS RELATED TO THE FOLLOW-UP OF PATIENTS WITH REMOVABLE PROSTHESES - Grădinaru Irina; Tărniceriu Cristina Claudia; Hurjui Loredana Liliana; Hurjui Ion; Balcoș Carina; Antohe Magda Ecaterina (Romanian Dental Association for Education, 2020)
The purpose of the study was to analyze and quantify the factors involved in the adaptation process to removable prostheses related to the patients' general condition and the number of visits to the dental medicine cabinet during the monitoring period. The study involved 85 patients, diagnosed with partially extended edentation, who reported to the Educational Center of the Faculty of Dental Medicine, Iasi, between 2018 and 2020 in view of reconstructing the integrity of their dental arches. The patients' age ranged between 38 and 79 and the study lot comprised 50 women and 35 men. The removable prostheses included partially removable acrylic prostheses in a percentage of 51%, partially removable skeletal prostheses in a percentage of 25% and partially removable flexible prostheses in a percentage of 24%. Planning oral health services will be a challenge for the professions in the dental medicine, with the impact of the increase of focus on dental unit loss on the subjective evaluation of patients of their own health and life quality. It is clear that the research in this field is not sufficient and that well-coordinated studies are necessary to address the impact of the use of partial skeletal removable prostheses on oral dental health.